1999
DOI: 10.4269/ajtmh.1999.60.188
|View full text |Cite
|
Sign up to set email alerts
|

Differential serodiagnosis for cystic and alveolar echinococcosis using fractions of Echinococcus granulosus cyst fluid (antigen B) and E. multilocularis protoscolex (EM18).

Abstract: Abstract. Echinococcus granulosus cyst fluid and E. multilocularis protoscolex extract were fractionated by a single step of preparative isoelectric focusing, resulting in an antigen B-rich fraction (8-kD) and an Em18-rich fraction, respectively. The usefulness of both fractions for differential serodiagnosis of cystic (CE) and alveolar (AE) echinococcosis was evaluated by a large-scale immunoblot analysis on a battery of 354 serum samples. These included 66 from AE patients originating from four different end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 28 publications
4
68
0
4
Order By: Relevance
“…These antigens can discriminate between E. granulosus and E. multilocularis in 95-97% of cases [77][78][79][80].…”
Section: Serologymentioning
confidence: 99%
“…These antigens can discriminate between E. granulosus and E. multilocularis in 95-97% of cases [77][78][79][80].…”
Section: Serologymentioning
confidence: 99%
“…Eight and 24 kDa antigens were also detected and accepted as specific in this study. As described in previous reports (7,14,15), the smallest subunit of antigen B (8 kDa) is highly sensitive and is expected to be Echinococcus genus specific (7). Our immunoblotting results, obtained with cyst fluid from sheep and donkey indicated that all the sera of mice infected secondary hydatidosis reacted with the antigen B subunit (8 kDa) in cyst fluid.…”
Section: Discussionmentioning
confidence: 79%
“…Antigenic profiles of protoscolices, fluid and germinal layer of cyst hydatids were studied by Western blotting in many studies and got different results due to host differences (5,6,7,13,16). In general hydatid cyst fluid (HCF) is collected from naturally infected intermediate hosts such as sheep, cattle, horses, camels, pigs or moose or from CE patients for preparation of purified native antigens (5,6,7,13,14). However, the nature and quality of the antigens are variable among the host species (12,15).…”
Section: Introductionmentioning
confidence: 99%
“…Serolojik testler, AE'nin tanısında, E.granulosus'un neden olduğu kistik ekinokokkoz (KE)'a kıyasla daha güvenilir olmaktadır. KE tanısında kullanılan Ag5 ve AgB antijenlerinin, diğer parazitlerin benzer molekülleriyle ortak epitoplara sahip olmasından ve KE hastalarının büyük oranının tüm majör E.granulosus antijenlerine karşı seronegatif olmasından dolayı, KE'nin serolojik tanısı AE'deki kadar özgül ve duyarlı olmamaktadır 11 . AE tanısında kullanılan testlerin duyarlılığı %82-97 arasında olup, saflaştırılmış ve/veya rekombinant özgül antijenler kullanıldığında özgüllüğü oldukça yüksek (%94-100) düzeylere ulaşmaktadır 12,13 .…”
Section: Introductionunclassified